PEMEROLEHAN PRAGMATIK PADA ANAK USIA TIGA TAHUN: STUDI KASUS PADA NASHA - Cindiana, Karis; Rakhmawati, Ani (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
Language acquisition is a natural process that children experience when learning their mother tongue, taking place gradually from simple to complex. This study aims to examine the pragmatic acquisition of three-year-old bilingual children, focusing on speech acts, conversational rules, implicatures, deixis, and violations of the principle of cooperation in Grice's maxims. The research subject is Nasha, a girl from a bilingual family who speaks Indonesian and Javanese. The method used is descriptive qualitative, including interviews and direct observation. The results show that Nasha shows basic pragmatic abilities although she still has limitations in understanding social and linguistic contexts. This research provides new insights into language development in early childhood, especially in the aspect of pragmatics in a bilingual environment.